2013
DOI: 10.4050/jahs.58.022001
|View full text |Cite
|
Sign up to set email alerts
|

Predictions of Brownout Dust Clouds Compared to Photogrammetry Measurements

Abstract: Results from a Lagrangian-Lagrangian-based brownout simulation were compared to photogrammetric measurements of the evolving dust clouds generated by a helicopter during low altitude taxi-pass and approach-to-touchdown maneuvers. An inviscid-viscous method was used to represent the carrier phase from a combination of the rotor flow field (modeled as an inviscid flow using a free-vortex wake) and a semiempirical boundary layer flow model at the ground. The mobilization and initial uplift of dust particles were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…Both saltation bombardment and reingestion bombardment processes were modeled in the present simulations. The dust cloud simulation used in the present study has been shown to exhibit good agreement with the measured evolution of actual brownout clouds [36].…”
Section: B Dust Cloud Modelingmentioning
confidence: 70%
See 2 more Smart Citations
“…Both saltation bombardment and reingestion bombardment processes were modeled in the present simulations. The dust cloud simulation used in the present study has been shown to exhibit good agreement with the measured evolution of actual brownout clouds [36].…”
Section: B Dust Cloud Modelingmentioning
confidence: 70%
“…The dynamic motion of these particles is then modeled in synchronicity with the solution for the rotor flow, as well as in the subsequent interactions of particles with the sediment bed. For example, dust particles in saltation or those that are reingested through the rotor disk can impact the sediment bed with greater momentum and eject many more particles in a process called bombardment [2,36,37]. Both saltation bombardment and reingestion bombardment processes were modeled in the present simulations.…”
Section: B Dust Cloud Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the graph, the particle sizes are shown near the bottom in frequency equivalent to that of electro-magnetic radiation whose wavelength is equal to the particle diameter. Actual particle sizes [7][8][9][10] are tabulated in Table 3. The obscurants listed above cause multiple scattering with the result that at shorter wavelengths, most of the detected photons have been scattered many times off the obscurant particles resulting in essentially zero contrast signals.…”
Section: Figure 2 Atmospheric Absorption and Obscurant Penetration Vermentioning
confidence: 99%
“…Computational approaches, such as the computational fluid dynamics (CFD) work performed by Kalra [31] and Thomas [43], attempt to model the brownout problem numerically. Several other CFD studies searched for ways to reduce the problem [44][45][46]. CFD can be useful as it allows for the investigation of many different aspects of brownout physics that can be hard to model in the laboratory, but experiments also necessary.…”
Section: Prior Workmentioning
confidence: 99%